Rethinking the actor's body dialogues with neuroscience - McCaw, Dick (Methuen Drama, 2020)
How does an actor embody a character? How do they use their body as an instrument of expression? Rethinking the Actor's Body offers an accessible introduction to the fields of neurophysiology and embodied knowledge through a detailed examination of what an actor does with their body. Built on almost a decade of conversations and public seminars by the author Dick McCaw in partnership with John Rothwell (Professor of Neurophysiology at University College London, UK), Rethinking the Actor's Body explores a set of questions and preoccupations concerning the actor's body and examines overlaps in research and practice in the fields of actor training, embodied knowledge and neurophysiology"--